2009
DOI: 10.1103/physrevb.80.241406
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of the graphene/4H-SiC(0001) interface probed by scanning current spectroscopy

Abstract: The current transport across the graphene/4H-SiC interface has been investigated with nanometric lateral resolution by scanning current spectroscopy on both epitaxial graphene ͑EG͒ grown on ͑0001͒ 4H-SiC and graphene exfoliated from highly oriented pyrolytic graphite deposited on the same substrate ͓deposited graphene ͑DG͔͒. This study reveals that the Schottky barrier height ͑SBH͒ of EG/ 4H-SiC ͑0.36Ϯ 0.1 eV͒ is ϳ0.49 eV lower than the SBH of DG/ 4H-SiC ͑0.85Ϯ 0.06 eV͒. This result is discussed in terms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 23 publications
6
70
0
Order By: Relevance
“…The device was then measured immediately after the cleaning process and five days later (whilst stored in a desiccator with <20% relative humidity), where transport measurements revealed n-type behavior with n e = 2.55 × 10 12 and n e = 4.71 × 10 11 cm −2 , respectively. The restored n-type conductivity of cleaned 1 LG on SiC(0001) is consistent with theory and experimental work presented by various other groups [6,102,103]. Table 2.…”
Section: Influence Of External Conditionssupporting
confidence: 90%
“…The device was then measured immediately after the cleaning process and five days later (whilst stored in a desiccator with <20% relative humidity), where transport measurements revealed n-type behavior with n e = 2.55 × 10 12 and n e = 4.71 × 10 11 cm −2 , respectively. The restored n-type conductivity of cleaned 1 LG on SiC(0001) is consistent with theory and experimental work presented by various other groups [6,102,103]. Table 2.…”
Section: Influence Of External Conditionssupporting
confidence: 90%
“…Recent nanoscale measurements of the current transport across EG/4H-SiC ͑0001͒ interface indicated that a laterally inhomogeneous distribution of positive charge is associated to these dangling bonds between the ZL and the bulk substrate. 21 This interface charge can explain both the lower average value and the larger spread in the local l gr values in the case of EG-SiC than in the case of DG-SiC. It is also worth noting that l gr on DG/SiC is on average ϳ4ϫ than on DG/SiO 2 and the spread of the l gr values are comparable in the two cases.…”
mentioning
confidence: 78%
“…19 We used optical contrast microscopy and atomic force microscopy to identify single layers of graphene ͑SLG͒ on DG-SiO 2 and on DG-SiC, 20 while micro-Raman spectroscopy along with conductive atomic force microscopy was used to identify SLG in EG-SiC. 21 The electron mean free path at room temperature was "locally" evaluated at different positions on the SLG by a recently demonstrated approach based on capacitance measurements made with the probe of a scanning capacitance microscope. 6 In the case of DG-SiO 2 , the SiO 2 film works as the gate dielectric and the n + Si substrate works as the semiconductor of a metal-insulator-semiconductor capacitor.…”
mentioning
confidence: 99%
“…Also, by operating in current spectroscopy mode, i.e., by performing local I-V measurements, the Schottky barrier height (SBH) of epitaxial graphene grown on H-SiC was estimated to be 0.36 ± 0.1 eV, which is 0.49 eV lower than the barrier of graphene exfoliated from HOPG and deposited on the same substrate (0.85 ± 0.06 eV). The result was explained as a Fermi-level pinning effect above the Dirac point in epitaxial graphene due to the presence of positively charged states [87]. Similarly, C-AFM allowed the mapping of the spatial inhomogeneities of the SBH and the ideality factor of contacts on MoS 2 , due to spatial variations in the density and energy of MoS 2 surface states, and to correlate local resistivity with local SBH [88].…”
Section: Electrical Modesmentioning
confidence: 99%